Method for producing nano silicon, negative electrode active material for lithium ion battery, negative electrode for lithium ion battery and lithium ion battery

By adjusting the atomic ratio of aluminum and magnesium in aluminosilicate and performing reduction treatment in an argon atmosphere, the generation problem of amorphous SiO2 and spinel in nanosilicon is solved, and the preparation of high-purity nanosilicon is achieved , avoids hydrofluoric acid treatment and is suitable for negative electrode materials for lithium-ion batteries.

CN116508173BActive Publication Date: 2024-12-24FIMATEC LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280006654.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-21
Filing Date
2022-09-21
Publication Date
2024-12-24
Estimated Expiration
2042-09-21

AI Technical Summary

Technical Problem

In the existing nanosilicon manufacturing method, there is unreduced nanosilicon residue and amorphous SiO2 generation, resulting in low purity of nanosilicon and an unsafe and costly hydrofluoric acid treatment process is required.

Method used

By adjusting the atomic number ratio of aluminum to magnesium in aluminosilicate and performing reduction treatment in an argon atmosphere, the formation of amorphous silica and spinel is inhibited, and hydrofluoric acid treatment is avoided, so as to achieve high efficiency nanosilicon preparation.

Benefits of technology

The preparation of high-purity nano-silicon is realized, which avoids the safety and cost problems of hydrofluoric acid treatment, and improves the yield and particle size uniformity of nano-silicon, which is suitable for the negative electrode material of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116508173B_ABST
    Figure CN116508173B_ABST
Patent Text Reader

Abstract

A method for producing nano-silicon comprises: (a) a process of reducing an aluminosilicate having an Al2O3 content of 3 to 40% by mass, wherein the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is within the range of 1:3.5 to 1:65; and (b) a process of acid-treating the reduced aluminosilicate obtained in step (a).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing nano-silicon. Specifically, the present invention relates to a method for producing nano-silicon by making aluminum oxide (Al 2 O 3 ) remains a certain amount, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is adjusted to an appropriate range and then reduced, thereby effectively producing a method for refined nano-silicon. Background Art

[0002] There are various methods for producing nanosilicon. As a production method using halloysite (alumina mineral) as a nanotube mineral product as a raw material, the following method is known: halloysite of a specific size is subjected to thermal acid treatment to cause alumina to flow out, NaCl or other alkali metal chlorides and / or alkaline earth metal chlorides as a heat absorber and magnesium powder as a reducing agent are mixed with the obtained nanosilicon dioxide, the temperature is increased to 600-1000°C at a specific heating rate in an argon atmosphere for reduction, and the nanosilicon is obtained by treating with dilute acid and then hydrofluoric acid (Patent Document 1).

[0003] However, in this method, unreduced nanosilicon will remain, and part of the nanosilicon obtained in the reduction reaction will be oxidized again to become silicon dioxide during subsequent water washing and acid treatment. Therefore, a process of finally treating with hydrofluoric acid to make the silicon dioxide flow out is required.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: China Patent Publication No. 105905908 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the experimental results conducted by the present inventors showed that in the above-mentioned prior art, the aluminum oxide content after the thermal acid treatment was 0 mass %, and even when the aluminum oxide content was 2 mass %, SiO 2 The reduction efficiency to Si is also low, and amorphous SiO 2 It is speculated that a large amount of amorphous SiO 2 In addition, the need to use hydrofluoric acid for treatment has significant disadvantages in terms of safety and cost.

[0009] Therefore, the problem to be solved by the present invention is to provide a method for producing high-purity nanosilicon, which suppresses the formation of amorphous silicon dioxide and suppresses the production of by-products such as spinel as compounds of aluminum, magnesium, etc. that may be synthesized during the reduction reaction by residual alumina, thereby eliminating the need for a hydrofluoric acid treatment step; and also provide a negative electrode active material comprising nanosilicon produced by the production method, a negative electrode for a lithium ion battery comprising the above-mentioned negative electrode active material, and a lithium ion battery comprising the above-mentioned negative electrode.

[0010] Methods for solving problems

[0011] The present inventors found that, in the process of repeatedly conducting experiments while changing various conditions, by intentionally making Al 2 O 3 Some or all of the residues remain, rather than making Al 2 O 3 All of it flows out from the raw material aluminosilicate mineral to form nanosilicon, so that the reduction process becomes efficient and nanosilicon can be stably refined. Moreover, by adjusting the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step to an appropriate range, the generation of impurities such as compounds of aluminum, magnesium, etc. is suppressed, thereby completing the present invention.

[0012] That is, the present application provides the following inventions.

[0013] 1. A method for producing nano-silicon, comprising: (a) treating Al 2 O 3 (a) a process of reducing an aluminosilicate having a content of 3 to 40% by mass, wherein the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is in the range of 1:3.5 to 1:65; and (b) a process of acid-treating the reduced aluminosilicate obtained in step (a).

[0014] 2. The production method according to item 1 above, wherein the ratio of the number of atoms is 1:3.7 to 1:45.

[0015] 3. The production method according to item 1 above, wherein the ratio of the number of atoms is 1:3.7 to 1:30.

[0016] 4. The production method according to any one of 1 to 3 above, wherein the aluminosilicate used in step (a) is halloysite or is obtained by dealumination of halloysite.

[0017] 5. The production method according to any one of 1 to 4 above, wherein the aluminosilicate used in step (a) is obtained by dealuminating the Al 2 O 3The content of the aluminosilicate is adjusted to 3 to 40% by mass.

[0018] 6. The production method according to 5 above, wherein the dealumination treatment includes an acid treatment selected from the group consisting of hot sulfuric acid treatment, sulfuric acid treatment, hydrochloric acid treatment, hot hydrochloric acid treatment, nitric acid treatment, hot nitric acid treatment, and combinations thereof.

[0019] 7. The production method according to any one of 1 to 6 above, wherein the reduced aluminosilicate obtained in step (a) contains 6 to 39 mass % of Al 2 O 3 .

[0020] 8. A manufacturing method according to any one of 1 to 7 above, wherein the reduction treatment in step (a) comprises: mixing magnesium powder as a reducing agent, one or more selected from the group consisting of alkali metal chlorides and alkaline earth metal chlorides as an endothermic agent, and the above-mentioned aluminosilicate, and heating the obtained mixture for reduction in an argon or nitrogen atmosphere.

[0021] 9. The production method according to any one of 1 to 8 above, wherein the acid treatment in step (b) uses at least one acid selected from the group consisting of hydrochloric acid, sulfuric acid, and nitric acid.

[0022] 10. The production method according to any one of 1 to 9 above, wherein the acid used in step (b) is hydrochloric acid, and the concentration thereof is 0.5 to 2.0 mol / liter.

[0023] 11. A method for producing nano-silicon, comprising: treating aluminosilicate with hot sulfuric acid to obtain Al 2 O 3 The process of preparing an aluminosilicate having a content of 3 to 40% by mass and subjecting the aluminosilicate to a reduction treatment; and the process of subjecting the reduced aluminosilicate obtained in the above process to an acid treatment.

[0024] 12. A negative electrode active material for a lithium ion battery, comprising nano-silicon obtained by the production method according to any one of 1 to 11 above.

[0025] 13. A negative electrode active material for a lithium ion battery, comprising nano-silicon, wherein the nano-silicon does not contain amorphous SiO2 as confirmed by diffraction X-ray analysis. 2 There was no halo, no spinel peak confirmed by diffraction X-ray analysis, and the primary particle size measured by a field emission scanning electron microscope was 10 to 15 nm.

[0026] 14. A negative electrode for a lithium ion battery, comprising the negative electrode active material according to 12 or 13 above.

[0027] 15. A lithium ion battery comprising the negative electrode for a lithium ion battery according to 14 above.

[0028] Effects of the Invention

[0029] Although not limited by any theory, the present invention is to make the conventional reducing agent such as Mg not only react with SiO2 present in the aluminosilicate, but also react with the conventional reducing agent such as Mg to form a reductant. 2 The reduction process is made more efficient by reducing the silicon dioxide by two routes (i.e., a route using a reducing agent such as Mg introduced from the outside and a new reducing agent such as Al generated by the reduction of the reducing agent) and also contacting with intentionally remaining aluminum oxide to reduce the aluminum oxide to form Al, and using the obtained aluminum also for the reduction of silicon dioxide, thereby preventing the Si generated by the reduction from being oxidized again to SiO 2 , silicon can be stably refined. In addition, when alumina is in excess relative to magnesium as a reducing agent, impurities such as spinel, which is a compound containing aluminum and magnesium and cannot be removed by acid, are generated. If impurities such as spinel are present, they cannot be removed in the subsequent acid treatment, and therefore remain as impurities, and the purity of nano-silicon is reduced. By appropriately adjusting the ratio of the number of atoms of aluminum contained in the aluminosilicate to the number of atoms of magnesium used as a reducing agent in the reduction treatment step, efficient reduction can be performed, and the generation of impurities such as spinel generated by the reaction of aluminum and magnesium and which cannot be removed in the acid treatment can be suppressed. According to the present invention, it is believed that by reducing aluminosilicate with aluminum and magnesium at an appropriate ratio, SiO 2 The reduction efficiency of Si is improved, the generation of compounds such as aluminum and magnesium such as amorphous silicon dioxide and spinel is suppressed, and the nano silicon obtained by reduction is not oxidized again, so the yield of nano silicon can be improved. According to the manufacturing method of the present invention, nano silicon can be obtained without performing a hydrofluoric acid treatment process. The obtained nano silicon is high-purity and has a small particle size, so it can be used as a negative electrode material for lithium ion batteries with excellent cycle characteristics, and a lithium ion battery containing it. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the X-ray diffraction pattern of the solid matter obtained in Examples 1 to 3.

[0031] Figure 2 This is an X-ray diffraction diagram of the solid matter obtained in Comparative Examples 1 to 3.

[0032] Figure 3 This is a photograph of the solid material obtained in Example 1 observed using a field emission scanning electron microscope. DETAILED DESCRIPTION

[0033] <Step (a): Containing 3 to 40 mass % of Al 2 O 3 Reduction treatment of aluminosilicates

[0034] Aluminosilicate is a salt formed by replacing part of Si in silicate with Al. I 2 O·yAl 2 O 3 ·zSiO 2 ·nH 2 O (Among them, metals also have M II Aluminosilicates are naturally present in large quantities in the form of minerals such as micas, feldspars, zeolites, and clays. Among them, halloysite, a clay mineral, is non-toxic and highly safe. The raw material aluminosilicate used in the present invention is not particularly limited, but halloysite with a small primary particle size and a high specific surface area in the natural state is preferred. The high specific surface area enables the reduction treatment to be effectively performed.

[0035] Aluminosilicates have various structures such as chain, layer, network, and tubular. In the present invention, from the perspective of the ease of reduction reaction, it is preferred to use aluminosilicates that are powdered by a jet mill, a roller mill, etc. The average particle size of the aluminosilicate powder is not particularly limited. From the perspective of the ease of reduction treatment and cost, it is preferably 1 to 20 μm, and more preferably 2 to 5 μm. It should be noted that the average particle size of the aluminosilicate is the particle size of the agglomerated particles, which can be measured under dry powder conditions using a laser diffraction particle size distribution measuring device (e.g., Malvern, Mastersizer 3000) using a dry disperser (e.g., Malvern, Aero S).

[0036] The raw material aluminosilicate of the present invention is Al 2 O 3 Aluminosilicate having a content of 3 to 40 mass %. By using Al 2 O 3 The subsequent reduction efficiency is improved, which can reduce the residual SiO 2 Furthermore, oxidation of Si in the subsequent acid treatment step (b) can be prevented. The aluminum oxide content is preferably 5 to 40% by mass, more preferably 6 to 39% by mass, and even more preferably 6 to 20% by mass.

[0037] It is believed that the Al contained in halloysite 2 O 3 The content of Al is about 35 to 40% by mass, regardless of the origin of the halloysite. Therefore, when using halloysite as the raw material aluminosilicate, untreated halloysite can be used directly, or a raw material aluminosilicate can be used by appropriately treating Al with the halloysite. 2 O 3 The content of halloysite is adjusted to the above preferred range.

[0038] As Al in aluminosilicate 2 O 3 The method for adjusting the content of Al can be, for example, a dealumination treatment, specifically, a hot sulfuric acid treatment. Specifically, the Al content can be controlled by adjusting the sulfuric acid concentration, the mass ratio of sulfuric acid to aluminosilicate, the reaction temperature, the reaction time, etc. 2 O 3 For example, Al can be obtained by treating 100 g of halloysite with 1200 g of sulfuric acid having a concentration of 25 mass % at 90° C. for 4 hours. 2 O 3 Halloysite with a content of 18%. If the treatment time is set to 5 hours under the same conditions, Al 2 O 3 The content can be 15%, 6% if set to 7 hours, and 2% if set to 14 hours. After the hot sulfuric acid treatment, it is typically preferred to wash with water according to a conventional method. It should be noted that according to the disclosure of Example 1 of the Chinese Patent Publication No. 105905908, when 5g of halloysite is treated with 500g of 2 mol / L (17.2 mass%) sulfuric acid at 100°C for 10 hours, Al 2 O 3 The content becomes 0%.

[0039] The dealumination treatment can be performed not only by hot sulfuric acid treatment but also by sulfuric acid treatment, hydrochloric acid treatment, hot hydrochloric acid treatment, nitric acid treatment, and hot nitric acid treatment.

[0040] The reduction treatment may use magnesium as a reducing agent.

[0041] Regarding the reducing agent, it is usually assumed that the Al in the raw aluminosilicate 2 O 3 All other than SiO 2 , preferably using magnesium powder in a molar ratio of 1 to 3 relative to the amount thereof. In addition, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is preferably 1:3.5 to 1:65, more preferably 1:3.7 to 1:45, and further preferably 1:3.7 to 1:30. When the number of magnesium atoms used as a reducing agent in the reduction treatment step is too small relative to the number of aluminum atoms contained in the aluminosilicate, compounds of aluminum and magnesium such as spinel that cannot be removed by acid will be generated, and when it is too large, amorphous silica will be generated.

[0042] Alkali metal chlorides and alkaline earth metal chlorides act as heat absorbers. That is, SiO 2When the reaction with the reducing agent (e.g., Mg) is an exothermic reaction, the Si obtained after the reduction will melt and condense due to the heat of reaction. In the present invention, by performing the reduction treatment in the presence of an alkali metal chloride or an alkaline earth metal chloride, the rise in the reaction temperature can be suppressed, and the reaction temperature is prevented from exceeding the melting point of silicon, and as a result, the condensation of the generated silicon can be suppressed.

[0043] Examples of the alkali metal chloride include NaCl and KCl. From the viewpoint of availability and cost, NaCl is preferred.

[0044] Examples of alkaline earth metal chlorides include CaCl 2 MgCl 2 From the perspective of availability and cost, CaCl is preferred. 2 .

[0045] As the endothermic agent, from the viewpoint of easy availability and cost, an alkali metal chloride is preferred, and among them, NaCl is preferred.

[0046] In order to effectively suppress aggregation, it is preferred to use a sufficient amount of the heat absorbent so that the heat absorbent does not reach the melting point of silicon due to the heat of reaction. However, if the amount is too much, the reduction reaction will be difficult to proceed, so it is preferred to use an appropriate amount. For example, it is desirable to use a heat absorbent with a mass ratio of 1 or more, preferably 9 or more, relative to the raw material aluminosilicate. If the amount is increased, the reduction reaction will be difficult to proceed, so the upper limit is preferably 12 or less in terms of mass ratio.

[0047] Relative to the SiO in the raw aluminosilicate 2 It is preferred to use magnesium powder or aluminum powder in a molar ratio of 1 to 3 and NaCl in a mass ratio of 8 to 12 relative to aluminosilicate in terms of the effect of the reduction treatment and the cost.

[0048] The reduction treatment can be performed by heating the aluminosilicate in which a specific amount of aluminum oxide remains in the presence of the reducing agent and the endothermic agent in an argon or nitrogen atmosphere.

[0049] The reduction conditions can be appropriately set by those skilled in the art. The above-mentioned heating is performed in a temperature range of, for example, 500 to 1000° C., preferably 500 to 800° C. The above-mentioned heating time is, for example, 1 to 24 hours, preferably 2 to 6 hours. From the perspective of the effect and cost of the reduction treatment, it is preferred to heat at 500 to 800° C. and within 6 hours, for example, about 3 hours, under an argon atmosphere.

[0050] As described above, the present invention can also be understood as a method for reducing aluminosilicate minerals to extract silicon, and therefore can also be referred to as a method for producing refined or smelted nano-silicon.

[0051] After reduction, it is typically preferred to wash with water by conventional methods to remove the heat absorbent. After washing with water, the washing water may be replaced with ethanol and then heated to disperse the ethanol. In this way, water can be removed more fully.

[0052] <Step (b): Acid treatment of solid matter after reduction treatment>

[0053] This step removes by-products of the reduction reaction, such as aluminum oxide, magnesium oxide, and their reaction products.

[0054] The acid used in this step is not particularly limited as long as it can achieve the above-mentioned purpose. For example, at least one acid selected from the group consisting of hydrochloric acid, sulfuric acid and nitric acid can be used. Among them, hydrochloric acid is preferred because it is relatively safe and easy to remove the neutralization salt by washing with water.

[0055] From the viewpoint of effect and safety, the concentration of the acid is preferably 0.3 to 8 mol / liter, more preferably 0.5 to 2.0 mol / liter.

[0056] In particular, from the viewpoint of sufficient reaction and higher safety, it is preferred to use 0.5 to 2.0 mol / liter of hydrochloric acid.

[0057] The amount of the acid is not particularly limited, and can be used in an amount sufficient to dissolve by-products such as aluminum oxide and magnesium oxide in the reduction step.

[0058] After the acid treatment, it is typically preferred to wash with water by a conventional method. After washing with water, the washing water may be replaced with ethanol, or the washing water may be heated to disperse the ethanol. In this way, water can be removed more fully.

[0059] [Anode material for lithium-ion battery and lithium-ion battery]

[0060] The nano silicon of the present invention can be used as a negative electrode active material of a lithium ion battery and is suitable for use in a negative electrode material, and can be suitable for use in a lithium ion battery containing the negative electrode material. The lithium ion battery is composed of a positive electrode formed by laminating a positive electrode active material on a positive electrode collector and a negative electrode formed by laminating a negative electrode active material on a negative electrode collector, and a secondary battery separator and an electrolyte are sandwiched between them.

[0061] The negative electrode for lithium ion battery of the present invention preferably has a negative electrode active material layer and a negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and an electrolyte containing an electrolyte and a solvent. The negative electrode active material layer may be composed only of the negative electrode active material of the present invention, or may be composed of a combination of the negative electrode active material of the present invention and a known negative electrode active material, and may further comprise known materials such as a binding material, a conductive material and an electrolyte, depending on the circumstances.

[0062] As known negative electrode active materials that can be used in combination with the negative electrode active material of the present invention, carbon materials such as graphite, hard carbon and soft carbon can be listed. In the case of using a known negative electrode active material in combination, for example, if the negative electrode active material of the present invention: the known negative electrode active material is used in a mass ratio of 1:2 to 1:30, then when the ratio of the negative electrode active material of the present invention is too low, the increase in the negative electrode capacity becomes less, and when the ratio is too high, if the charge and discharge are repeated, it will cause a decrease in the capacity of the negative electrode (a decrease in the cycle characteristics). It should be noted that when the negative electrode active material of the present invention is carbon-coated using sucrose or the like as a raw material, the capacity of the negative electrode active material of the present invention can be efficiently exerted. The above-mentioned mass ratio in this case represents the ratio of the total amount of the net mass of the negative electrode active material of the present invention and the mass of the carbon coating to the mass of the known negative electrode active material.

[0063] As the binder, carboxymethyl cellulose, styrene butadiene rubber latex, starch, polyvinylidene fluoride, polyvinyl alcohol, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene and other known solvent drying type binders for lithium ion batteries can be listed. When the binder is used, it is preferably used in an amount of 1 / 100 to 1 / 5 relative to the total amount of the negative electrode active material.

[0064] Examples of the conductive material include acetylene black, graphite, Ketjen black, carbon black, etc. When the conductive material is used, it is preferably used in an amount of 1 / 100 to 1 / 3 of the total amount of the negative electrode active material.

[0065] Examples of the electrolyte include LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 and LiN(FSO 2 ) 2 Lithium salts of inorganic anions such as LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 and LiC(CF 3 SO 2 ) 3 Lithium salts of organic anions.

[0066] As the solvent, propylene carbonate, ethylene carbonate, 1,2-dimethoxyethane, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, cyclopentane, acetonitrile, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, etc. can be cited. The solvent can be used alone or in combination of two or more. As the additive in the solvent, vinylene carbonate, fluoro vinylene carbonate, methyl vinylene carbonate, fluoromethyl vinylene carbonate, ethyl vinylene carbonate, propyl vinylene carbonate, butyl vinylene carbonate, dimethyl vinylene carbonate, diethyl vinylene carbonate, dipropyl vinylene carbonate, vinyl acetate, butyrate vinylene, caproate vinylene, crotonate vinylene, catechol carbonate, propane sultone, butane sultone, etc. can be cited. The additive can be used alone or in combination of two or more.

[0067] The nano-silicon obtained by the production method of the present invention can be used for various purposes, and is preferably used as a negative electrode material for lithium-ion batteries.

[0068] The nano-silicon obtained by the production method of the present invention usually has a primary particle size as small as about 10 to 15 nm. Figure 3 The nano-silicon obtained by the production method of the present invention also does not contain amorphous SiO2 as confirmed by diffraction X-ray analysis. 2 There is no halo, nor is there a peak of spinel confirmed by diffraction X-ray analysis. That is, according to the present invention, high-purity nano silicon can be obtained. When Si is used as the negative electrode material of a lithium ion battery, the volume change caused by the entry and exit of lithium ions leads to micronization, and capacity reduction becomes a problem. However, if the silicon particles are small, it is not easy to micronize due to volume change, and the negative electrode of a lithium ion battery with excellent cycle characteristics can be obtained. If the particle size is uniform, the gap between the particles becomes larger, and the cycle characteristics become excellent.

[0069] In addition, in this specification, "%" means "mass %" unless otherwise specified.

[0070] Example

[0071] <Pretreatment 1-Hot sulfuric acid treatment>

[0072] 1200 g of 25% aqueous sulfuric acid solution was heated to 90°C, and 100 g of dry-crushed halloysite powder (trade name DRAGONITE-HP, manufactured by Applied Minerals, average particle size 12 μm) was added under stirring. In order to prevent the sulfuric acid concentration from changing significantly due to water evaporation, the mixture was covered with a lid and stirred at 90°C for 5 hours.

[0073] Then, the remaining solid matter is collected on the filter paper by suction filtration. Distilled water is further added to the captured solid matter, suction filtration is continued, and the filtrate is washed with water until the ionic conductivity of the filtrate is less than 30μS / cm. In this way, sulfuric acid and water-soluble reaction products are removed from the solid matter. After the solid matter is dried at 120°C for 24 hours, it is crushed with an air flow mill (SJ-100CB manufactured by Nissin Engineering Co., Ltd.) to obtain a white powder of aluminosilicate with an average particle size of about 3μm. In accordance with JIS R2216: Fluorescent X-ray Analysis Method for Refractory Products, a fluorescent X-ray analyzer (ZSX PrimusII manufactured by Rigaku Corporation) was used to measure the aluminosilicate by a standard curve method using glass beads, and it was confirmed that it contained 15% Al 2 O 3 .

[0074] <Pretreatment 2-Hot sulfuric acid treatment>

[0075] The same treatment as in Pretreatment 1 was performed except that the reaction time was changed to 14 hours to obtain a white powder of aluminosilicate. The aluminosilicate was measured in the same manner as in Pretreatment 1 and it was confirmed that it contained 2% Al 2 O 3 .

[0076] <Pretreatment 3-Hot sulfuric acid treatment>

[0077] The same treatment as in Pretreatment 1 was performed except that the reaction time was 7 hours to obtain a white powder of aluminosilicate. The aluminosilicate was measured in the same manner as in Pretreatment 1 and it was confirmed that it contained 6% Al 2 O 3 .

[0078] <Pretreatment 4-Non-thermal sulfuric acid treatment>

[0079] Without reacting the halloysite powder with heated sulfuric acid, the dry-pulverized halloysite powder (trade name DRAGONITE-HP, manufactured by Applied Minerals, average particle size 12 μm) was pulverized with an air flow mill (SJ-100CB manufactured by Nissin Engineering Co., Ltd.) to obtain a white powder of aluminosilicate with an average particle size of about 3 μm. The aluminosilicate was measured in the same manner as in pretreatment 1, and it was confirmed that it contained 39% Al 2 O 3 .

[0080] <Example 1>

[0081] (mixing with NaCl, drying)

[0082] 41.48 g of NaCl and 137 mL of distilled water were mixed with 4.88 g of the aluminosilicate prepared in Pretreatment 1, and the mixture was stirred at room temperature for 1 hour. Then, the solvent was evaporated under reduced pressure using a rotary evaporator, and the mixture was dried at 120° C. for 12 hours.

[0083] (Mixed with Mg)

[0084] The obtained dried product was crushed into powder using an agate mortar. 8.94 g of the obtained powder was taken out and 0.72 g of [SiO 2 :Mg≈1:2.2 (mol ratio)](Al 2 O 3 All other than SiO 2 Mg powder (calculated) was added to the above powder and mixed. At this time, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step was 1:10.7.

[0085] (Reduction reaction)

[0086] Put all the obtained mixture into an alumina crucible and place it in an electric furnace. Then, after reducing the pressure in the electric furnace, repeat the Ar gas injection 3 times ((decompression → Ar gas injection) × 3) to replace the electric furnace with Ar gas. While Ar gas is continuously flowing in the electric furnace, heat to 580°C at a heating rate of 10°C / min, and then heat to 600°C at a heating rate of 1°C / min. After maintaining at 600°C with Ar gas flowing for 3 hours, cool down to 40°C, then slowly replace the Ar gas in the electric furnace with air, and take out the alumina crucible.

[0087] (Water wash)

[0088] A large amount of water is added to the solid matter in the removed alumina crucible, ultrasonic waves are applied to the liquid for 10 minutes, and then the supernatant is removed after centrifugation. This operation (water addition → ultrasonic waves → centrifugation) is repeated 3 times to remove NaCl. Then, the solid matter is recovered onto filter paper by suction filtration, ethanol is added to the solid matter, and suction filtration is performed to replace the water present in the solid matter with ethanol. Then, the solid matter on the filter paper is heated at 60°C under reduced pressure for 3 hours to remove ethanol and obtain a brown solid matter.

[0089] (HCl treatment)

[0090] The obtained brown solid was slowly added to 100 mL of 1 M hydrochloric acid solution. After all the solution was added, the mixture was allowed to stand for 4 hours.

[0091] (Water wash)

[0092] Then, a large amount of water was added, and the supernatant was removed after centrifugation. After repeating this operation (water addition → ultrasonic wave → centrifugation) 3 times, the solid was recovered on the filter paper by suction filtration. Then, ethanol was added to the recovered solid, and suction filtration was performed, thereby replacing the water present in the solid with ethanol. Then, the solid on the filter paper was heated at 60°C for 3 hours under reduced pressure to remove ethanol and obtain a brown solid.

[0093] The obtained brown solid was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 1 No amorphous SiO was observed. 2 A halo at 2θ=20-25° appeared when the sample was taken. A peak believed to be derived from quartz, a natural aluminosilicate, was slightly observed. A tiny peak from the aluminum sample holder was also confirmed.

[0094] Observation using a field emission scanning electron microscope (JSM-6700F manufactured by JEOL) revealed that the diameter of the primary particles of silicon was approximately 10 to 15 nm ( Figure 3 ). Si, Al, and O were subjected to SEM-EDX analysis (SEM: Hitachi High-Tech Scanning Electron Microscope SU3500, EDX: Horiba EMAXEvolution EX-370X-MAX20 energy dispersive X-ray analyzer) to measure the atomic number concentration (%). The result showed that the residual oxygen atomic number concentration was 21.49%. The results are shown in Table 1.

[0095] <Example 2>

[0096] The starting material is the aluminosilicate obtained in pretreatment 3, NaCl is 46.07 g, and distilled water is 148 mL. In the mixing step with Mg, the amount of the powder mixed with NaCl, dried and crushed is set to 8.85 g (at this time, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is 1:29.7). Except for this, a brown solid is obtained by the same operation as in Example 1.

[0097] The obtained brown solid was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 1 No amorphous SiO was observed. 2 A halo at 2θ=20-25° appeared when the sample was taken. A peak believed to be derived from quartz, a natural aluminosilicate, was slightly observed. A tiny peak from the aluminum sample holder was also confirmed.

[0098] <Example 3>

[0099] The starting material was the aluminosilicate obtained in pretreatment 4, 29.96 g of NaCl, 103 mL of distilled water, and in the mixing step with Mg, the amount of the powder mixed with NaCl, dried and crushed was set to 9.30 g, and the amount of Mg powder was set to 0.94 g [SiO 2 :Mg≈1:2.90 (mol ratio)](Al 2 O 3 All other than SiO 2 Calculation) (at this time, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is 1:3.9), the amount of 1M hydrochloric acid solution used in the HCl treatment step is set to 160mL, and a brown solid is obtained by the same operation as in Example 1.

[0100] The obtained brown solid was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 1 No amorphous SiO was observed. 2 A halo at 2θ=20-25° appeared when the sample was taken. A peak believed to be derived from quartz, a natural aluminosilicate, was slightly observed. A tiny peak from the aluminum sample holder was also confirmed.

[0101] <Example 4>

[0102] The brown solid (nano silicon) 10.4g, sucrose 5.2g, methanol 59.1g and distilled water 25.3g obtained in Example 1 were crushed in a mortar to prepare a suspension. The suspension was dried at an inlet temperature of 100°C using a micro-mist spray dryer (GF) to obtain a powder. The powder was dried at 60°C under reduced pressure for 2 hours, and then heated at 800°C for 2 hours under an Ar atmosphere to carbon-coat the brown solid (nano silicon).

[0103] 0.85 g of the brown solid (nanosilicon) after carbon coating was mixed with 7.65 g of graphite so that the mass ratio of the active material of the negative electrode material was silicon:graphite=1:9. The obtained active material mixture, 1.00 g of acetylene black as a conductive material, 20 g of an aqueous solution of carboxymethyl cellulose (1% mass percentage concentration) as a binder, 0.74 g of styrene-butadiene rubber latex (40.4 mass percentage concentration), and 1.20 g of distilled water were stirred and mixed to obtain a suspension with a mass percentage concentration of 31.8%. The suspension was applied to Cu foil and dried at 120°C for 10 hours using a vacuum dryer and then punched into a diameter of 17 mm. It was used as a working electrode (negative electrode) to make a basic evaluation cell (half-cell) under the conditions of Table 1, and the unipolar characteristics were measured under the charge and discharge conditions shown in Table 1. The unipolar characteristics are shown in Tables 3 and 4.

[0104] [Table 1]

[0105]

[0106] <Comparative Example 1>

[0107] The starting material is the aluminosilicate obtained in pretreatment 2, NaCl is 48.06 g, and distilled water is 154 mL. In the mixing step with Mg, the amount of the powder mixed with NaCl, dried and crushed is set to 8.81 g (at this time, after mixing with Mg, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is 1:93.0). Except for this, a brown solid is obtained by the same operation as in Example 1.

[0108] The obtained brown solid was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 2 ). Amorphous SiO 2 When present, a halo of 2θ=20~25° appears.

[0109] Si, Al, and O were subjected to SEM-EDX analysis (SEM: Hitachi High-Tech Scanning Electron Microscope SU3500, EDX: Horiba, Ltd. Energy Dispersive X-ray Analyzer EMAXEvolution EX-370X-MAX20) to measure the atomic number concentration (%), and the residual oxygen atomic number concentration was 51.71%. The results are shown in Table 1.

[0110] <Comparative Example 2>

[0111] The starting material was the aluminosilicate obtained in Pretreatment 2, and the reduction treatment time by heating at 600°C in an Ar gas atmosphere was 24 hours. A brown powder was obtained by the same operation as in Comparative Example 1. At this time, after mixing with Mg, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step was 1:93.0.

[0112] The obtained brown powder was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 2 ). Amorphous SiO 2 When present, a halo of 2θ=20~25° appears.

[0113] Observation was performed using a field emission scanning electron microscope (JSM-6700F manufactured by JEOL), and the primary particles of silicon were 20 to 60 nm. SEM-EDX analysis (SEM: Hitachi High-Tech Scanning Electron Microscope SU3500, EDX: Horiba Energy Dispersive X-ray Analyzer EMAXEvolution EX-370X-MAX20) was performed on Si, Al, and O to measure the atomic number concentration (%). The residual oxygen was 56.65% in terms of atomic number concentration. The results are shown in Table 1.

[0114] <Comparative Example 3>

[0115] The amount of Mg powder added as a reducing agent in the mixing step with Mg is 0.72 g [SiO 2 :Mg≈1:2.2 (mol ratio)](Al 2 O 3 All other than SiO 2 Calculation) (at this time, after mixing with Mg, the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is 1:3.0), except for this, a brown powder is obtained by the same operation as in Example 3.

[0116] The obtained brown solid was analyzed by diffraction X-ray, and a clear peak of silicon was observed ( Figure 1 No amorphous SiO was observed. 2 The halo at 2θ = 20-25° appears when the quartz is quartz. Peaks believed to be derived from natural aluminosilicates are observed. Spinel (MgAl 2 O 4 ) peak.

[0117] <Comparative Example 4>

[0118] A basic evaluation cell (half cell) was prepared under the same conditions as in Example 4 except that the silicon used in the working electrode was commercially available carbon-coated 100 nm silicon, and the unipolar characteristics were measured under the charge and discharge conditions shown in Table 1. The unipolar characteristics are shown in Tables 3 and 4.

[0119] [Table 2]

[0120]

[0121] [Table 3]

[0122]

[0123] [Table 4]

[0124]

[0125] according to Figure 2 The measurement results of the diffraction X-ray analysis shown in the figure confirmed that: the Al 2 O 3 When the ratio of the number of atoms of aluminum contained in the aluminosilicate to the number of atoms of magnesium used as a reducing agent in the reduction treatment step is 1:93.0, the more amorphous SiO 2 The halo of amorphous SiO 2 The more there is (Comparative Examples 1 and 2). The reduction time of Example 1 is 3 hours, while the reduction time of Comparative Example 2 is 24 hours. However, even when the reduction time is extended to 24 hours, amorphous SiO is clearly observed. 2 Halo (Comparative Example 2, Figure 2 ). In addition, according to Figure 2 The measurement results of the diffraction X-ray analysis shown in the figure show that Al 2 O 3 When the ratio of the number of atoms of aluminum contained in the aluminosilicate to the number of atoms of magnesium used as a reducing agent in the reduction treatment step was 1:3.0, spinel (MgAl 2 O 4 ) (Comparative Example 3).

[0126] In contrast, after the pre-treatment 1, 3, 4 operations, Al 2 O 3 When the content of SiO2 was adjusted to 6%, 15%, and 39%, and the ratio of the number of atoms of aluminum contained in the aluminosilicate to the number of atoms of magnesium used as a reducing agent in the reduction treatment step was adjusted to 1:29.7, 1:10.7, and 1:3.9, and then the reduction treatment was performed (Examples 1 to 3), no amorphous SiO2 was observed within 3 hours of reduction. 2 The halo, spinel (MgAl 2 O 4 ) of the peak( Figure 1 ). Furthermore, the primary particle size of silicon in Example 1 is 10 to 15 nm, which is smaller than that in Comparative Example 2.

[0127] In the case of obtaining high-purity silicon, in Comparative Examples 1 and 2, amorphous SiO 2 The amorphous SiO 2 The presence of a halo is necessary to obtain high-purity silicon by using hydrofluoric acid to remove amorphous SiO 2Furthermore, as in Comparative Example 3, when the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step is 1:3.0, when the amount of aluminum is excessive relative to the amount of magnesium, spinel (MgAl) is generated, which cannot be removed even by acid treatment. 2 O 4 However, by performing the reduction treatment in a suitable range of the ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step as in Examples 1 to 3, it was obtained by diffraction X-ray analysis that there was no amorphous SiO 2 The mass % of oxygen was calculated based on the atomic concentrations of O, Al, and Si in Example 1, and it was 13.49 mass %. If the density of silicon is 2.33, SiO 2 The density of the nano-silicon is set to 2.3, and the primary particle size of the nano-silicon is set to 10 nm. Then, the SiO 2 The thickness of the film is about 0.5 nm. For example, even when the nano-silicon of Example 1 is used as the negative electrode material of a lithium ion battery, the SiO 2 The thickness will not hinder the lithium ions and electrons from entering and exiting the nano-silicon. Therefore, according to the present invention, even if the extremely dangerous and costly hydrofluoric acid is not used to treat the amorphous SiO 2 By removing the step, it is possible to obtain high-purity nano-silicon that can be used as a negative electrode material for lithium-ion batteries, for example.

[0128] The basic evaluation battery (half-cell) was actually made and the charge and discharge cycle test was carried out. The result was: the lithium-ion battery (Example 4) in which the silicon obtained by the present invention was carbon-coated and matched with the working electrode (negative electrode) was compared with the lithium-ion battery (Comparative Example 4) in which the commercially available 100-nanometer silicon was carbon-coated and matched with the working electrode. Although the carbon coating amount of silicon was larger in Example 4, or the initial capacity was smaller than that of Comparative Example 4, the capacity retention rate in the cycle test was excellent. The battery capacity was also higher in the embodiment after the fifth cycle. When silicon is used as the negative electrode material of a lithium-ion battery, it is micronized due to the volume change caused by the entry and exit of lithium ions, and the capacity reduction becomes a problem. However, it is believed that the size of the silicon particles obtained in the present invention is very small, 10 to 15 nanometers, and it is not easy to be micronized due to volume changes, and the capacity retention rate in the cycle test is excellent.

Claims

1. A method for producing nano-silicon, comprising: (a) a step of reducing an aluminosilicate having an Al2O3 content of 3 to 40% by mass in a ratio of the number of aluminum atoms contained in the aluminosilicate to the number of magnesium atoms used as a reducing agent in the reduction treatment step within a range of 1:3.5 to 1:65; and (b) A step of treating the reduced aluminosilicate obtained in the step (a) with an acid.

2. The manufacturing method according to claim 1, wherein: The ratio of the number of atoms is 1:3.7 to 1:

45.

3. The manufacturing method according to claim 1, wherein: The ratio of the number of atoms is 1:3.7 to 1:

30.

4. The production method according to any one of claims 1 to 3, wherein The aluminosilicate used in the step (a) is halloysite or is obtained by dealumination of halloysite.

5. The production method according to any one of claims 1 to 3, wherein The aluminosilicate used in step (a) is an aluminosilicate whose Al2O3 content is adjusted to 3 to 40% by mass by dealumination.

6. The manufacturing method according to claim 5, wherein: The dealumination treatment includes an acid treatment selected from the group consisting of hot sulfuric acid treatment, sulfuric acid treatment, hydrochloric acid treatment, hot hydrochloric acid treatment, nitric acid treatment, hot nitric acid treatment, and combinations thereof.

7. The production method according to any one of claims 1 to 3, wherein The reduced aluminosilicate obtained in step (a) contains 6 to 39 mass % of Al 2 O 3 .

8. The production method according to any one of claims 1 to 3, wherein The reduction treatment in step (a) includes mixing magnesium powder as a reducing agent, one or more selected from the group consisting of alkali metal chlorides and alkaline earth metal chlorides as an endothermic agent, and the aluminosilicate, and heating the obtained mixture in an argon or nitrogen atmosphere for reduction.

9. The production method according to any one of claims 1 to 3, wherein The acid treatment in step (b) uses at least one acid selected from the group consisting of hydrochloric acid, sulfuric acid, and nitric acid.

10. The production method according to any one of claims 1 to 3, wherein: The acid used in step (b) is hydrochloric acid, and its concentration is 0.5 to 2.0 mol / liter.

11. A method for producing nano-silicon, comprising: A step of treating aluminosilicate with hot sulfuric acid to obtain aluminosilicate having an Al2O3 content of 3 to 40% by mass, and performing a reduction treatment on the aluminosilicate; and A step of treating the reduced aluminosilicate obtained in the above step with an acid.